Awareness day on the importance and conservation of the Ziziphus tree - Hamrouni Bel Hadj Brahim, Lamia; Ouled Belgacem, Azaiez; Hassan, Sawsan; Louhaichi, Mounir (International Center for Agricultural Research in the Dry Areas, 2023)
Silvopastoral systems, integrating tree cultivation with livestock grazing, offer sustainable agricultural practices with environmental benefits. This study explores the vital role of Ziziphus species in Tunisian silvopastoral systems, emphasizing their ecological, economic, and cultural significance. The genus, comprising Ziziphus lotus, Ziziphus spina-christi, and Ziziphus mauritaniana, contributes to soil conservation, water retention, and biodiversity enhancement. Economic benefits include nutritional fruits, medicinal resources, and income generation. Despite their multifunctionality, there's a need for awareness and proper management. This report outlines the proceedings of an awareness day, facilitated by experts, aimed at highlighting the importance of Ziziphus and addressing challenges. Recommendations focus on research, awareness campaigns, environmental education, and legislative support for sustainable Ziziphus cultivation.